Meningkatkan Hasil Belajar Fase F Materi Hierarki Dalam Gereja Katolik Bernalar Kritis Model PBL SMKN 1 Monterado - Artanius Artanius (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The researcher is a State Teacher at SMK Negeri 1 Monterado, Bengkayang Regency, West Kalimantan, in the subject of Catholic Religious Education. This research is Classroom Action Research which aims to improve student learning outcomes and critical reasoning in learning using the Problem Based Learning (PBL) learning model or Problem Based Learning (PBM). The point is whether the PBL Learning Model can be effectively applied in the classroom, especially in the Class The method used was Classroom Action Research in 2 implementation cycles on class XI students at SMKN 1 Monterado, using discussion and question and answer methods in problem solving of real problems encountered. Based on the research results, it was found that the problem-based learning system by applying the discussion and question and answer method, was felt to be quite effective and could improve learning outcomes, find the source of problems, analyze the sources of problems and attempt to solve problems encountered and Critical Reasoning. For this reason, this method is very suitable to be applied to arouse students' enthusiasm for learning and bring out students' creativity in learning.